Efficacy and safety evaluation of neoadjuvant immunotherapy plus chemotherapy for resectable non–small cell lung cancer in real world - Fang, Min; Hang, Qingqing; Jiang, Haitao; Cai, Lei; Hu, Jinlin; Ying, Hangjie; Gu, Qing; Yu, Xiaofu; Liu, Jinshi; Lai, Xiaojing (Frontiers in Oncology, 2023)
Objectives The combination of immunotherapy and chemotherapy has shown great efficacy in stage IV non–small cell lung cancer (NSCLC) and is now widely used in clinical treatment strategy. This study retrospectively analyzed the efficacy and safety of neoadjuvant immunotherapy plus chemotherapy for resectable NSCLC in real world. Methods We retrospectively analyzed patients with NSCLC who received neoadjuvant immunotherapy plus chemotherapy and underwent complete tumor resection in Zhejiang Cancer Hospital between January 2019 and January 2021. Tumor staging was based on the eighth TNM classification system of the American Joint Committee on Cancer staging criteria. The safety and toxicity (including operative and postoperative complications) and the efficacy [including objective response rate (ORR), disease control rate (DCR), tumor major pathological remission (MPR), and pathological complete response (pCR)] were evaluated. Results In total, 368 patients with NSCLC were administered with neoadjuvant immunotherapy. Of them, 211 patients were included in this retrospective study. Most patients had stage II–III disease, with 75 (35.5%) and 88 (41.7%) patients diagnosed with clinical stages IIB and IIIA, respectively. A total of 206 patients (97.6%) received at least two doses of neoadjuvant immunotherapy plus chemotherapy. In addition, 121 patients (57.3%) have achieved MPR, and 80 patients (37.9%) have achieved pCR, with ORR at 69.2% and DCR at 97.7%. Treatment-related adverse events occurred in 46.4% of patients, and the incidence rate of grade 3 or 4 treatment-related adverse events was 13.3% (13/98). Moreover, adverse events of any grade of surgical complication occurred in 15.6% of patients. One-year disease-free survival was 80.6% (170/211). Conclusions Neoadjuvant immunotherapy plus chemotherapy has significant efficacy with a high pCR and tolerable adverse effects for patients with resectable stage II–III NSCLC in real world.